Boron templated synthesis of a BODIPY analogue from a phthalocyanine precursor. (11th May 2016) - Crandall, Laura A.; Rhoda, Hannah M.; Nemykin, Victor N.; Ziegler, Christopher J.
Abstract : The synthesis of aza(dibenzopyrro)methenes (ADBMs) using aryl boron compounds as templates is described. Compounds (1–3 ) are structurally related to the BODIPYs and were isolated with terminal imine, oxo, or mixed imine-oxo groups. Compounds1–3 were investigated for their absorption/emission properties, and were probed by DFT and TDDFT methods. Abstract : The synthesis of aza(dibenzopyrro)methenes (ADBM) using aryl boron compounds as templates is described. The resultant half phthalocyanine BPh2 compounds (1–3 ) are structurally related to the BODIPY class of fluorophores and were isolated with terminal imine, terminal oxo, or mixed imine-oxo heteroatom positions. Compounds1–3 were investigated for their absorption/emission properties, and large stokes shifts of ∼50 nm were observed for fluorescence emission. The electronic structures of1–3 were probed by TD/DFT methods.